Predictive biomarkers of response to anti-EGF receptor monoclonal antibody therapies. (April 2014) - Kumar, Shalini Sree; Price, Timothy J; Townsend, Amanda R; Hocking, Christopher; Hardingham, Jennifer E
SUMMARY : The EGF receptor (EGFR) pathway plays an important role in the progression of several carcinomas, including colorectal cancer (CRC). The EGFR has emerged as a candidate for targeted therapy for CRC. Two monoclonal antibodies used to inhibit the EGFR signaling pathway are cetuximab and panitumumab. Both these monoclonal antibodies inhibit tumor-promoting activities, such as tumor cell proliferation, survival, angiogenesis and metastasis. However, only a subpopulation of metastatic CRC patients responds to such therapy. Constitutive activation within the pathway gives rise to other aberrantly expressed biomarkers that are able to circumvent the anti-EGFR treatment and confer resistance. Mechanisms of resistance and the value of these emerging predictive biomarkers in the clinical setting are discussed in this review.